Behavior and ecology of Macaca leonina (Mammalia: Primates) at Ha Noi Zoo, Vietnam - Nguyen, Thanh Vinh; Nhai, Tong Thi (Academia Journal of Biology, 2018)
Northern Pigtailed Macaque (Macaca leonina) naturally distributes in southern Vietnam, where it adapts to high daily temperature. In Ha Noi Zoo, northern Vietnam, time budget and diet of a 10-individual group of Macaca leonina and some ecological factors (temperature, humidity, human impact) were studied to determine its adaptation to the weather in the northern region of the country. Methods for the present study comprise focal time sampling and ad libitum. The study results showed that the species activities are not influenced by temperature and humidity, but strongly impacted by humans. There were linear regressions between the human impact and several activities of the species.